2020
DOI: 10.3390/ma13051164
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Profile Wideband Linear-to-Circular Polarization Conversion Slot Antenna Using Metasurface

Abstract: A new low-profile wideband linear-to-circular polarization conversion microstrip slot antenna based on a metasurface for C-band satellite communication applications is proposed in this paper. The metasurface basically consists of four unit cells with parasitic square cross gaps arranged in a 2 × 2 layout. By loading the metasurface on the microstrip slot antenna, linearly polarized (LP) waves from the source antenna are converted into circularly polarized (CP) waves. Then, by etching three more parasitic squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…In [15], an antenna with potential application in satellite communications was developed by coupling a metasurface to a microstrip antenna. The metasurface basically consists of four unit cells with parasitic square crossed gaps in an array of 2 × 2 elements.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], an antenna with potential application in satellite communications was developed by coupling a metasurface to a microstrip antenna. The metasurface basically consists of four unit cells with parasitic square crossed gaps in an array of 2 × 2 elements.…”
Section: Previous Workmentioning
confidence: 99%
“…The aim is to achieve an antenna that operates from 5.1 GHz to 7.2 GHz with high gain in the entire band. The proposed structure is easy to build, inexpensive and compact compared to most previous configurations [6], [11] and has a higher bandwidth compared to [13], [15]. The results of the studies show that the metasurface characteristics and the unit cell pattern change the antenna impedance resulting in the overlapping of the new resonant frequencies, which allow a measured fractional bandwidth of 45.4 % (5.1 -8.0 GHz).…”
mentioning
confidence: 91%
“…Metasurfaces (MS), which is the 2-D equivalent of metamaterials, are being utilized presently for various antenna applications. [4][5][6][7][8][9][10][11] Not only they are used to improve the antenna performance in terms of gain 4 and bandwidth (BW), 5 but they are also used for antenna parameter (polarization, frequency or pattern) reconfiguration 6 and converting the polarization state of an antenna from linear to circular. [7][8][9][10][11] They have also proved to play a crucial role in reducing the antenna RCS owing to their extraordinary electromagnetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Not only they are used to improve the antenna performance in terms of gain 4 and bandwidth (BW), 5 but they are also used for antenna parameter (polarization, frequency or pattern) reconfiguration 6 and converting the polarization state of an antenna from linear to circular. [7][8][9][10][11] They have also proved to play a crucial role in reducing the antenna RCS owing to their extraordinary electromagnetic behavior. 12 Initially, a combination of artificial magnetic conductors (AMC) and perfect electric conductors (PEC) structures was most commonly used for RCS reduction of antennas.…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle for polarization conversion performance is decomposing incident wave into two components, orthogonal to each other but having the same magnitudes and phase difference as ±90˚. This concept has been used in different types of LP-to-CP converters which have been reported using non-resonant [12][13][14] and resonant periodic structures [15][16][17][18][19][20][21]. For example, Euler et al reported frequency selective surface based polarization converter using a single layer of the substrate [15].…”
Section: Introductionmentioning
confidence: 99%